Effectiveness of case-area targeted interventions including vaccination on the control of epidemic cholera: protocol for a prospective observational study. Issue 7 (6th July 2022) - Ratnayake, Ruwan; Peyraud, Nicolas; Ciglenecki, Iza; Gignoux, Etienne; Lightowler, Maria; Azman, Andrew S; Gakima, Primitive; Ouamba, Jean Patrick; Sagara, Joseph Amadomon; Ndombe, Rollin; Mimbu, Nana; Ascorra, Alexandra; et al.
Abstract : Introduction: Cholera outbreaks in fragile settings are prone to rapid expansion. Case-area targeted interventions (CATIs) have been proposed as a rapid and efficient response strategy to halt or substantially reduce the size of small outbreaks. CATI aims to deliver synergistic interventions (eg, water, sanitation, and hygiene interventions, vaccination, and antibiotic chemoprophylaxis) to households in a 100—250 m 'ring' around primary outbreak cases. Methods and analysis: We report on a protocol for a prospective observational study of the effectiveness of CATI. Médecins Sans Frontières (MSF) plans to implement CATI in the Democratic Republic of the Congo (DRC), Cameroon, Niger and Zimbabwe. This study will run in parallel to each implementation. The primary outcome is the cumulative incidence of cholera in each CATI ring. CATI will be triggered immediately on notification of a case in a new area. As with most real-world interventions, there will be delays to response as the strategy is rolled out. We will compare the cumulative incidence among rings as a function of response delay, as a proxy for performance. Cross-sectional household surveys will measure population-based coverage. Cohort studies will measure effects on reducing incidence among household contacts and changes in antimicrobial resistance. Ethics and dissemination: The ethics review boards of MSF and the London School of Hygiene and Tropical Medicine have approved a generic protocol. The DRC and Niger-specific versions have been approved by the respective national ethics review boards. Approvals are in process for Cameroon and Zimbabwe. The study findings will be disseminated to the networks of national cholera control actors and the Global Task Force for Cholera Control using meetings and policy briefs, to the scientific community using journal articles, and to communities via community meetings.